Impact of surface morphology on the properties of light emission in InGaN epilayers. (25th April 2018) - Uždavinys, Tomas Kristijonas; Marcinkevičius, Saulius; Mensi, Mounir; Lahourcade, Lise; Carlin, Jean-François; Martin, Denis; Butté, Raphaël; Grandjean, Nicolas
Abstract: Scanning near-field optical microscopy was used to study the influence of the surface morphology on the properties of light emission and alloy composition in InGaN epitaxial layers grown on GaN substrates. A strong correlation between the maps of the photoluminescence (PL) peak energy and the gradient of the surface morphology was observed. This correlation demonstrates that the In incorporation strongly depends on the geometry of the monolayer step edges that form during growth in the step-flow mode. The spatial distribution of nonradiative recombination centers — evaluated from PL intensity maps — was found to strongly anticorrelate with the local content of In atoms in the InGaN alloy.